Effectiveness of nursing interventions for breathlessness in people with chronic obstructive pulmonary disease: A systematic review and meta‐analysis. (17th January 2019) - Steindal, Simen A.; Torheim, Henny; Oksholm, Trine; Christensen, Vivi L.; Lee, Kathryn; Lerdal, Anners; Markussen, Heidi Øksnes; Gran, Gerd; Leine, Marit; Borge, Christine Råheim
Abstract: Aim: To critically review and synthesize the findings of studies that evaluated the effectiveness of nursing interventions for improving breathlessness in adults with chronic obstructive pulmonary disease. Background: Systematic reviews of nursing interventions for breathlessness in people with chronic obstructive pulmonary disease have not been specifically addressed. Design: Systematic review with meta‐analysis. Data sources: A systematic search of Medline, CINAHL, PsycINFO and Embase was performed for studies published between January 2000 and June 2017. Review methods: Risk of bias, data extraction and meta‐analysis were conducted using Cochrane methodology. The quality of evidence was assessed using the GRADE approach. Results: Twenty papers were included. A meta‐analysis of interventions performed at home, including two trials, showed a significant effect in favour of experimental groups for the symptom score of the St. George Respiratory Questionnaire compared with controls. A meta‐analysis of interventions performed in clinics with home follow‐up showed a significant effect in favour of experimental groups for the mastery and fatigue scores of the Chronic Respiratory Questionnaire compared with controls. In this category of intervention, an additional meta‐analysis showed a significant effect in favour of experimental groups for the symptom, activity and total scores of the St. George Respiratory Questionnaire compared with controls. The quality of evidence was assessed to be very low to moderate. Conclusion: The results are equivocal as to whether nursing interventions performed at home and nursing interventions performed in hospital with follow‐up improve breathlessness in people with chronic obstructive pulmonary disease. Abstract : 目的: 批判性回顾和综合关于评估为改进患有慢性阻塞性肺病的成人气喘所采取的护理干预有效性的研究研究结果 背景: 对慢性阻塞性肺疾病患者呼吸困难的系统回顾护理干预措施尚未得到明确处理。 设计: 系统回顾和综合分析。 资料来源: 在2000年1月至2017年6月期间发表的研究中, 对联机医学文献分析和检索系统、护理学数据库、心理学文摘和荷兰医学文摘数据库进行了系统的搜索。 审核方法: 采用考科兰方法分析偏倚风险, 数据提取和综合分析。采用等级方法评估证据的质量。 结果: 包括20篇论文。对在家进行的干预措施进行综合分析, 包括两项试验, 结果显示, 与对照组相比, 圣乔治呼吸问卷的症状评分更有利于实验组。一项对门诊进行的家庭随访干预措施的综合分析显示, 与对照组相比, 实验组在慢性呼吸系统问卷的掌握程度和疲劳评分方面具有显著的优势。在这类干预中, 另一项综合分析显示, 与对照组相比, 圣乔治呼吸问卷的症状、活动和总分对实验组有显著的帮助。证据的质量被评估为非常低到中等水平。 结论: 对于在家进行的护理干预和在医院进行的随访护理干预是否能改善慢性阻塞性肺病患者的呼吸困难, 结果尚不明确。